Ambient Intelligence in the Production and Retail Sector: Emerging Opportunities and Potential Pitfalls - Röcker, Carsten (Proceedings of the International Conference on Innovation, Management and Technology (ICIMT'09))
This paper provides an introduction into the evolution of information and communication technology and illustrates its usage in the work domain. The paper is sub-divided into two parts. The first part gives an overview over the different phases of information processing in the work domain. It starts by charting the past and present usage of computers in work environments and shows current technological trends, which are likely to influence future business applications. The second part starts by briefly describing, how the usage of computers changed business processes in the past, and presents first Ambient Intelligence applications based on identification and localization information, which are already used in the production and retail sector. Based on current systems and prototype applications, the paper gives an outlook of how Ambient Intelligence technologies could change business processes in the future.
Keywords: Ambient Intelligence; Ubiquitous Computing; Business Applications; Radio Frequency Identification (RFID).